Students' Mathematical Critical Thinking Based on Self-Esteem Through Problem Based Learning in Geometry - Krida Singgih Kuncoro; Agustin Zakkia; Fitria Sulistyowati; Betty Kusumaningrum (SEAMEO Regional Centre for QITEP in Mathematics, 2021)
This study aims to describe and determine mathematical critical thinking skills based on students' self-esteem. This research used a mixed method with a sequential explanatory research design. The research population was first year mathematics education students who took geometry courses, and the research samples were selected by way of purposive sampling technique. Research subjects were grouped based on high, medium, and low self-esteem categories to be interviewed about students' critical thinking skills. The research instruments were tests and interviews. The results showed that students had various mathematical critical thinking skills in terms of self-esteem. Four students possessed a high level of self-esteem as indicated by the fact that two students’ mathematical critical thinking skills results were classified in high category while the remaining two students were in medium category. Of 25 students who had moderate self-esteem, 5 students obtained high category in the results of their mathematical critical thinking skills, 14 students had their result in moderate category students, and 6 students were in the low category. Of 3 students with low self-esteem, one student had their results of the mathematical critical thinking ability result in the high category and two students had their result in the low category. It can be concluded that there is less significant correlation between self-esteem and students' critical thinking skills. Meanwhile, there are three different levels in students' critical thinking skills in terms of self-esteem at high, medium, and low levels.